Evaluation of the Principal's Academic Supervision Program: Discrepancy Evaluation Model. - Shelva Kharisma Indiastuti; Bambang Ismanto (Mimbar Ilmu, 2023)
Quality education requires the role of the teacher. Academic supervision by the principal is required to ensure and improve the quality of teachers. However, many obstacles and inconsistencies arose during the supervision program’s implementation. This research aimed to examine the implementation of the principal’s academic supervision program. The program evaluation is carried out to assess the existence of discrepancies between the central government’s program standards and the actual conditions. Qualitative-descriptive with a discrepancy evaluation model developed by Malcolm Provus with 4 stages, namely design, installation, process, and product is the method chosen in this research. The subjects in this study were the principal and 13 teachers. Data was collected using interview, observation, and documentation techniques. Data analysis was performed using data reduction, data presentation, and conclusion drawing. The conclusion is that there are gaps in the academic supervision program made by the school at each stage of the discrepancy evaluation.